PENGARUH INTELLECTUAL CAPITAL DAN CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE TERHADAP KINERJA PERUSAHAAN - Chintya, Chintya (EQUITY, 2018)
The purpose of th is study was to test empirically the influence of Intellectual Capital and Corporate Sociall Responsibility Disclosure to the performance of companies in Indonesia. Intellectual capital is measured using Pulic method (VAIC) and Corporate Social Responsibility Disclosure measured by using CSDI (CSR Index). Company performance is proxied with company profitability that is measured by Return on Assets. Data used in this study is secondary data, consist of annual reports, financial reports, and sustainability reports. The sample used in this study was chosen by using purposive sampling method with the aim to get the sample according to the criteria. The sample in this study amounted to 76, which consisted of 19 manufacturing companies of the basic and chemiccal industry sectors during the period 2013 to 2016. The results showed that intellectual capital and corporate social responsibility disclosure positively affect the financial performance of the company